ANALISIS POTENSI DAN KENDALA EKSPOR PRODUK PERTANIAN INDONESIA: KAJIAN PUSTAKA - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse the potential and constraints of Indonesian agricultural product exports through a literature review. The results of the study indicate that Indonesia has enormous agricultural export potential, supported by rich natural resources, commodity diversity, and growing global demand. However, the utilisation of this potential is still constrained by various internal factors such as inconsistent product quality, inadequate infrastructure, and limited market access and certification. External factors such as global competition, differences in quality standards, and trade policies of destination countries also pose major challenges. To optimise agricultural product exports, a comprehensive strategy is needed, including improving product quality and certification, strengthening infrastructure, simplifying regulations, and developing market access and product branding. Collaboration between the government, businesses, and farmers is key to enhancing the competitiveness and contribution of the agricultural sector to the national economy.